Back Cover: Simultaneous quantification of perindopril erbumine, indapamide and amlodipine besylate in newer combination of anti‐hypertensive drugs in pharmaceutical dosage form by thin layer chromatography method. Issue 5 (12th May 2020) - Patel, Kirtan; Chhalotiya, Usmangani; Kachhiya, Hetaben; Patel, Jay; Shah, Dimal; Nagda, Dhruti
Abstract : DOI: 10.1002/sscp.202000010 The cover picture shows the HPTLC method developed for the simultaneous identification and quantification of Perindopril erbumine, Indapamide and Amlodipine besylate in bulk and pharmaceutical dosage form. According to ICH guidelines the method was validated and found to be sensitive, accurate and precise. Statistical analysis proved that method was repeatable and selective for the analysis of Perindopril erbumine, Indapamide and Amlodipine besylate without any interference from the excipients. The method was successfully used for the determination of drug in their pharmaceutical formulation.